A Genome-Wide Association Study Reveals Differences in the Genetic Mechanism of Control of the Two Gait Patterns of the Brazilian Mangalarga Marchador Breed - Fonseca, Mayara Gonçalves [UNESP]; Ferraz, Guilhermede Camargo [UNESP]; Lage, Jessica [UNESP]; Pereira, Guilherme Luis [UNESP]; Curi, Rogério Abdallah [UNESP] (Elsevier, 2017)
The DMRT3 gene is described as the main gene involved in the determination of gait phenotypes in horses, and the allele A of the 22999655C>A single nucleotide polymorphisms (SNP) has been reported as a causal variant of this trait. In the Mangalarga Marchador breed, which exhibits two gait patterns with well-defined characteristics, genotypes AA and CA are associated with marcha picada and genotype CC with marcha batida. In this breed, allele A of the DMRT3 gene is only related to the marcha picada gait. The objective of this study was to identify the type of control of the marcha batida gait and to investigate SNPs and genomic regions responsible for this phenotype in Mangalarga Marchador horses. Forty-eight horses belonging to the two gait groups, marcha picada with AA and CA genotypes of the 22999655C>A SNP (n = 20) and marcha batida with CC genotype (n = 28), were analyzed using the Equine SNP70 BeadChip. The genome-wide association study result shows for the first time that, in contrast to the marcha picada gait phenotype that is apparently determined by a single gene (DMRT3) in which allele A of variant g.22999655C>A controls the trait, the marcha batida gait is controlled by a larger number of genes. Because of the small number of animals used in the two groups compared, the genomic regions associated with smaller effects on the marcha batida gait could not be identified.
Keywords: DMRT3 gene; Gait; Genotyping; Horse